2021
DOI: 10.3390/ijerph18083965
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Attachment to Parents and Peers and the Use of Instagram: The Mediation Role of Psychopathological Risk

Abstract: Several studies have shown an association between adolescents’ attachment relationships and social media use. Instagram is the social media platform most used by teenagers and recent studies have shown an association between Instagram use and increased psychopathological risk. The present study aims to verify whether psychopathological risk mediates the relationship between an adolescent’s attachment to their parents and peers and their Instagram addiction. N = 372 adolescents are assessed through self-report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 72 publications
0
18
0
2
Order By: Relevance
“…Nevertheless, although a higher psychopathological risk among insecure adolescents has also been reported in the context of COVID-19 [49], our study is the first to explore the possible specific role played by attachment to mothers, fathers, and peers, showing a significant contribution exerted by late adolescents' attachment to fathers and peers. Unexpectedly, attachment to mothers was not significantly associated with late adolescents' peritraumatic distress due to COVID-19, although previous studies have widely shown the key role played by the quality of mother-child relationship in shaping offspring's psychopathological difficulties overtime [68,[93][94][95]. However, it is important to note that results of our preliminary correlation analyses have shown a significant association between late adolescents' attachment to mothers and alexihtymia, suggesting a possible indirect effect of attachment to mother on peritraumatic distress due to COVID-19 via late adolescents' alexithymia (a result discussed below).…”
Section: Main Findingsmentioning
confidence: 78%
“…Nevertheless, although a higher psychopathological risk among insecure adolescents has also been reported in the context of COVID-19 [49], our study is the first to explore the possible specific role played by attachment to mothers, fathers, and peers, showing a significant contribution exerted by late adolescents' attachment to fathers and peers. Unexpectedly, attachment to mothers was not significantly associated with late adolescents' peritraumatic distress due to COVID-19, although previous studies have widely shown the key role played by the quality of mother-child relationship in shaping offspring's psychopathological difficulties overtime [68,[93][94][95]. However, it is important to note that results of our preliminary correlation analyses have shown a significant association between late adolescents' attachment to mothers and alexihtymia, suggesting a possible indirect effect of attachment to mother on peritraumatic distress due to COVID-19 via late adolescents' alexithymia (a result discussed below).…”
Section: Main Findingsmentioning
confidence: 78%
“…Finally, the emerging adults’ family context was not considered. In fact, several studies have highlighted the psychological impact of the family on the origin of the youths’ mental health [ 105 , 113 , 117 , 151 , 152 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Bergen Instagram Addiction Scale (BIAS; [ 105 ]) was developed by adapting the Bergen Social Media Addiction Scale [ 106 , 107 ]. It is a 6-item self-report questionnaire developed to measure six core features of social media addiction: salience, mood modification, tolerance, withdrawal, conflict, and relapse.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the longitudinal study showed that Facebook intensity predicted a decline in self-concept clarity over time whereas a reverse pathway was not supported. The results suggest that an intense attachment to Facebook contributes to an inconsistent and unclear self-concept Ballarotto, Volpi, and Tambelli, [ 82 ] Italy 372 (15.8 ± 1.4) Bergen Instagram Addiction Scale (BSMAS) Cross-sectional Findings show that a worse attachment to parents and peers is associated with adolescents’ psychopathological risk, which is associated with Instagram addiction Best, Manktelow, and Taylor, [ 68 ] Ireland 527 (U) Warwick-Edinburgh Mental Well-Being Scale (WEMWBS), General Self-Efficacy Scale (GSE), ad hoc questions Cross-sectional Young males who reported speaking to online friends regarding personal problems recorded statistically significantly higher levels of mental well-being ( p < 0.02) Calancie et al, [ 51 ] Ontario 8 (15.5 ± U) Focus group Qualitative study Many participants reported a fear of receiving negative comments online and discussed strategies to avoid them, such as posting less content (i.e., comments, photographs) than their peers. Some participants described feeling positive emotions when they received a “like” from a SNS user, however, they also tended to describe these positive emotions as “false”, “unreal” and “fleeting.” Notably, many participants reported comparing themselves to peers on Facebook, which increased feelings of anxiety, as well as compulsive checking behaviours, such as monitoring posted content and friend lists Charmaraman et al, [ 81 ] USA 772 (12.6 ± 1.0) A combination of validated and self-created items Cross-sectional Quantity of social technology use (e.g., checking social media, problematic internet behaviors, mobile use), content viewed (e.g., emotional or violent videos, risky behaviors), and social context (e.g., bedtime behaviors, starting social media at an early age) were significantly related to later bedtimes and fewer hours of sleep on school nights.…”
Section: Methodsmentioning
confidence: 99%